Prognosis and long-term observation of a group of patients with acute coronary syndromes without ST-elevation (ACS-NSTEMI) - Katarzyna Kołodziej; Jarosław Drożdż; Małgorzata Kurpesa; Zbigniew Bednarkiewicz; Maria Krzemińska-Pakuła (Archives of Medical Science, 2006)
Introduction: The clinical assessment of patients with unstable angina is based not only on clinical symptoms, but also on concomitant diseases. The aim of this study was to investigate the adverse outcome in patients receiving successful treatment and discharged from the hospital. Material and methods: The study group consisted of 53 consecutive patients after an incident of unstable angina (62±11 years, 29 men, 55%), among whom 17 patients were diabetics (32%). On admission, 61 clinical, electrocardiographic, echocardiographic, angiographic and laboratory factors were taken into consideration. We analysed the frequency of recurrent myocardial infarctions, recurrent ischaemia, the need for revascularisation and deaths during the follow-up of 23±2 months. Results: The mortality rate was 9% and in 38% patients none of the above complications occurred. A univariate analysis revealed that age (p=0.005), diabetes mellitus (p=0.017), wall motion abnormalities in echocardiography (p=0.02), ST segment depressions on admission ECG (p=0.033), male gender (p=0.036) and the pattern of the mitral inflow (p=0.047) were predictors for adverse events. A multivariate analysis showed diabetes mellitus to be the strongest independent predictor of complicated outcomes (OR=9; p=0.008) beside a filling pattern of the mitral inflow (OR=1.9; p=0.03). The left ventricular end-diastolic diameter (p=0.016) was the only independent predictor of death. Conclusions: Diabetes is the strongest prognostic factor in patients after incidents of unstable angina. Therefore, such patients should be considered for more extensive medical care.